Выражение (3x+y)(x+y)-4y(x-y) (y-10)(y-2)+(y+4)(y-5)

hramkova1983 hramkova1983    2   27.09.2019 07:50    2

Ответы

(3x+y)(x+y)-4y(x-y) (y-10)(y-2)+(y+4)(y-5)=

=3х²+3ху+ух+у²-4у(ху-10х-у²+10у)(у-2)+у²+4у-5у-20=

=3х²+4ху+у²+4у(ху²-10ху-у³+10у²-2ху+20х+у²-20у)+у²-у-20=

=3х²+4ху+у²+4ху³-40ху²-4у⁴+40у³-8ху²+80ху+4у³-20у²+у²-у-20=

=3х²+84ху-18у²+4ху³-48ху²-4у⁴+44у³-у-20

(3x+y)(x+y)-4y(x-y)=3х²+3ху+ух+у²-4ху+4у²=3х²+5у²

(y-10)(y-2)+(y+4)(y-5)=у²-10у-2у+20+у²+4у-5у-20=2у²-13у

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра